EFFECTIVENESS OF CHEWING GUM AND TOOTHPASTE OF XYLITOL ON THE PLAQUE INDEX IN ADOLESCENT GROUP. - Henri Hartman; Andi Supriatna; Badi Soerachman; Raina Azzah Maliha (Fakultas Kedokteran Gigi Unjani, 2022)
Periodontal disease and caries are part of dental and oral health problems. The main cause of periodontal disease and caries is plaque. Dental plaque can be controlled with a combination of chemicals and mechanics treatment. The growth of dental plaque can be inhibited by using chemicals, namely xylitol which can be used in the form of chewing gum or toothpaste. Xylitol is a natural carbohydrate sweetener that cannot be fermented by bacteria in the oral cavity. Xylitol can accumulate Streptococcus mutans intracellularly and make Streptococcus mutans expends energy to break down accumulated xylitol without producing unfavorable energy. This research was conducted as literature study and analyzed the findings obtained. This literature review used six pieces of literature about xylitol chewing gum and two pieces of literature about xylitol toothpaste. Data analysis used Paired Samples T-Test of plaque index. The results showed that there was a statistically significant result (p<0,05) of the plaque index before and after using xylitol chewing gum. On the other hand, there was no significant result (p>0,05) on the plaque index before and after using xylitol toothpaste. The decreased plaque index was established in both of the xylitol types, but not meaningful when used in toothpaste. DOI : 10.54052/jhds.v2n1.p75-84